Parent-child communication and its perceived effects on the young child's developing self-concept - Yahaya, Azizi (2006)
The modern family is becoming stretched, due to the fast pace of living, stres, and time constraints that can impact on the quality of parent-child interactions. (Mustard & McCain:39,Bornstein,n.d.). In addition, the traditional autocratic parenting style is being challenged due to societyâ€™s move towards a more democratic style of parenting. As parents only want the best for their children, this shift has caused further stress and confusion as their parenting role and to what is expected by society. As a consequence of societyâ€™s high expectations, parents â€œfeel concerned and often their worry is passed on to the childrenâ€? who is turn may â€œ have very high expectations of themselves and become extremely tense and frightened of failureâ€? (Roe,1999:20).